The Utilization of Sawdust and Various Decomposers as Raw Materials for Organic Fertilizer Production - Sari Rukmana Okta Sagita Chan; Benny Satria Achmad; Rovel Lando Fambari; Eka Susila (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Sawdust is an abundant material in rural areas of Lima Puluh Kota Regency, making its utilization an effective way to prevent it from being wasted. Sawdust also has great potential to enrich soil with essential elements needed by plants. The process of making organic fertilizer typically involves the addition of microorganisms to accelerate the decomposition of organic materials. One of the challenges in producing and developing organic fertilizer is selecting the right decomposer to ensure that the composting process does not take too long and can be quickly applied and utilized by farmers. This study aims to identify the best decomposer capable of breaking down and accelerating the composting process of sawdust waste. The study used a Completely Randomized Design with the following treatments: sawdust:chicken manure (2:1) + bioactivator, sawdust:chicken manure (2:1) + bio tanduria, sawdust:chicken manure (2:1) + m21 dan sawdust:chicken manure (2:1) + Trichoderma sp. Observation parameters: compost maturation time (days), texture, color, moisture and temperature. From all observations of sawdust compost, treatment A2 (sawdust:chicken manure (2:1) + bio tanduria) showed the best results, and the composting time was also relatively short.